Dietary astaxanthin levels affect colour, growth, carotenoid digestibility and the accumulation of specific carotenoid esters in the Giant Tiger Shrimp, Penaeus monodon. (24th September 2015) - Wade, Nicholas M; Cheers, Sue; Bourne, Nicholas; Irvin, Simon; Blyth, David; Glencross, Brett D
Abstract: The carotenoid astaxanthin (Axn) plays a vital role in shrimp pigmentation, with direct influence on product quality, and forms a significant cost component of shrimp aquaculture feeds. However, the effects of dietary Axn on other measures of shrimp physiological performance are varied, and the efficiency of carotenoid uptake from the diet and deposition in shrimp tissues is poorly defined. This study fed juvenile shrimp ( Penaeus monodon ) diets that contained 0, 25, 50 or 100 mg kg −1 Axn for 6 weeks. Shrimp fed carotenoid‐free diets had significantly reduced colour and growth than those fed carotenoids, but survival was unaffected. Carotenoid digestibility improved as dietary carotenoid levels increased, and was 98.5% in shrimp fed 100 mg kg −1 Axn. After 6 weeks, whole body carotenoid levels were significantly depleted in 0 or 25 mg kg −1 fed shrimp, compared with those fed 50 or 100 mg kg −1 or compared with initial shrimp. This study also showed that Axn monoesters were enriched with saturated fatty acids, whereas Axn diesters were enriched with monounsaturated and polyunsaturated fatty acids. Combined, these studies demonstrate that a total dietary carotenoid intake of between 25 and 50 mg kg −1 Axn is required for normal shrimp growth and health in P. monodon . Evidence suggests that there is a functional role for the accumulation of carotenoids and the formation of specific Axn fatty acid esters, and these may be linked to the metabolism, storage, mobilization or deposition of Axn within various tissues.